The Representation of Radical Feminism in Black Widow Movie Directed by Cate Shortland - Sri Arfani; Juhana Juhana; Nurul Vitria Hastutik (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The goal of feminism is to fully establish gender equality in law and practice while combating sexism, sexist exploitation, and oppression. Cate Shortland is the director of the superhero science fiction film Black Widow. In the film, black widowed women are controlled by the Red Room Academy, a clandestine criminal organization. The primary character and former Black Widow Natasha Romanoff is depicted destroying the Red Room Academy and its male head, Dreykov. The theory of feminism and film analysis are used by the researcher to answer these research questions. There are three objectives in this research. The first objective is to describe the character value of Natasha in the movie. Next is to analyze the radical feminism shown by Natasha in the movie. Last, to analyze the moral value that the director wants to convey. This research was qualitative descriptive method by watching the movie and taking several scenes that were related to the theory. The results of this research reveal that: (1) There are three-character value from Natasha as the main character of the movie; independent, social care and perseverance. (2) The analysis reveals the radical feminism inclinations portrayed by Natasha Romanoff is the act of self-sacrifice. (3) The moral value found in Black Widow movie is about caring each other and women’s right.